(untitled) (Padmakanya Journal of Science and Technology, 2025)
The Manohara River, a vital tributary of the Bagmati River in Kathmandu Valley, Nepal, is heavily degraded due to urbanization and industrial activities. This study assesses seasonal variations in physicochemical parameters and Water Quality Index (WQI) at ten sites from Sankhu to Jadibuti during pre-monsoon (March 2024) and monsoon (August 2024). Parameters including pH, electrical conductivity (EC), total dissolved solids (TDS), dissolved oxygen (DO), biochemical oxygen demand (BOD), ammonia, and phosphate were analyzed using standard methods. Monsoon dilution reduced EC (704.3 to 260.7 μS/cm), TDS (351.9 to 130.1 mg/L), and BOD (327.5 to 128.46 mg/L), while DO improved (1.01 to 5.42 mg/L). However, high ammonia, phosphate, and BOD indicated persistent pollution. WQI values (213.86 pre-monsoon, 206.57 monsoon) classified the water as “Very Poor,” unfit for drinking or fish culture. Phosphate, ammonia, and low DO were key pollution drivers. Urgent pollution control and monitoring are needed to restore the river’s ecological health.